Answer: 25
<u>Step-by-step explanation:</u>
7(x - y) - 3(2 + 2x)
= 7x - 7y - 6 - 6x
= x - 7y - 6
for x = 3, y = -4
3 - 7(-4) - 6
= 3 + 28 - 6
= 31 - 6
= 25
Answer:
5≤u
Step-by-step explanation:
Put the words and numbers into an equation:
-5u+27≤2
Put all like terms on one side:
27-2≤5u ---> Do you see what I did there? Now you don't have to work with negatives. :)
Simplify:
25≤5u
Solve:
5≤u
:)
Answer: 948
Step-by-step explanation:
From the question, we are informed that 4-pound pumpkin will yield about 1.5 cups of mashed pumpkin (pumpkin puree).
Therefore, the number of cups of pumpkin puree that Steve Geddes' 2,528-pound pumpkin will yield will be:
= (2528/4) × 1.5
= 632 × 1.5
= 948 cups of pumpkin puree
Answer:
They are equal if that’s what you’re asking
Step-by-step explanation: